Divorce commentator : What it is.. And adapted Method and legal (Journal of the College of Education for Women, 2019)
Banned temporarily divers has increased greatly in the society and for silly reasons.This issue aroused a great controversy .There are so many motivations to Aleve deep in it.There are so many approach hes to talk it . It deserves to be studied in a simple way butthoroughly and comprehensively .Dune to this great importees and to its spread amongmarried couples for their agnorance concerning its voles' and dangers .I have been stimulated and encouraged to go through and close read its detailsaleomplish this research.It is a olevided in to an introduction and three chapters :1-chapter one : defines the terminology of banned temporarily clearer's and it legal situation .2-chapter two : Terms of banned temporarily devoirs, its results and devisions .3-chapter three : Religions and legal position of banned temporarily devours .Then the conclusion where results and recommendations are set clearly.